Digital Transformation of Land Services in Indonesia: A Case Study of Bogor, Sleman, and Buleleng - Kusmiarto, Kusmiarto; Wahyono, Eko Budi; Syaifullah, Arief; Wahyuni, Wahyuni; Sitorus, Oloan; Desmawan, Herdyn; Putra, Brahmantio Taufan Anata; Pratidina, Ni Putu Aris; Wulandari, Indah Yunita (Marcapada: Jurnal Kebijakan Pertanahan, 2025)
The digital transformation of land administration services in Indonesia through the Electronic Land Certificate Program represents a strategic government initiative aimed at improving efficiency, transparency, and legal certainty, as regulated under the Ministerial Regulation of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) No. 3 of 2023. However, its implementation faces multifaceted complexities and challenges at the local level. This study aims to conduct a comparative analysis of the implementation of the electronic land certificate program across four prioritized land offices: Sleman, Bogor I, Bogor II, and Buleleng—by identifying common patterns and specific differences in encountered issues and applied strategies. A descriptive qualitative approach with a comparative case study method was employed. Data were gathered through in-depth interviews, direct observations, and document analysis at each location. The findings reveal shared challenges, including poor data quality, limited human resources, suboptimal information technology infrastructure, and constrained policy and budget dynamics. Nonetheless, differences arise across local contexts: Sleman highlights case backlogs; Bogor I focuses on media conversion issues; Bogor II emphasizes the relationship between data quality and implementation effectiveness; while Buleleng centers on post-disaster archival reconstruction strategies. This research contributes to a more profound understanding of regional implementation gaps and offers adaptive policy recommendations to accelerate sustainable digital transformation within Indonesia’s national land administration system.